Investigation of biochemical characters and antioxidant properties of different winged bean (Psophocarpus tetragonolobus) genotypes grown in Indonesia - JANSON CALVINDI; MUHAMAD SYUKUR; Waras Nurcholis (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Calvindi J, Syukur M, Nurcholis W. 2020. Investigation of biochemical characters and antioxidant properties of different winged bean (Psophocarpus tetragonolobus) genotypes grown in Indonesia. Biodiversitas 21: 2420-2424. Winged bean, Psophocarpus tetragonolobus (L) DC, is described as having antioxidant properties. This work evaluated the biochemical and antioxidant characteristics of the P. tetragonolobus genotypes. Twelve-winged bean genotypes were calculated for total phenolic content (TPC) and total flavonoid content (TFC) of biochemical characters and antioxidant properties by using four methods: 2,2-diphenyl picrylhydrazyl (DPPH), cupric reducing antioxidant power (CUPRAC), ferric reducing antioxidant power (FRAP), and Trolox equivalent antioxidant capacity (TEAC). The plant material was grown in the same location conditions in Indonesia. The total phenolic content varied from 154.6 to 161.5 mg GAE/ 100 g, and flavonoid ranged from 105.2 to 112.4 mg QE/ 100 g fresh weight. The antioxidant capacities were 30.6 - 47.0, 140.4 - 167.6, 66.9 - 170.8, and 28.0 - 52.4 µmol TE/ 100 g fresh weight as calculated by the DPPH, TEAC, FRAP, and CUPRAC assays, respectively. The antioxidant activities were significantly correlated with the polyphenol content of winged bean genotypes fruits. The genotypes TU, L3, H3U, H1P, and TH were recognized higher based on their TPC, TFC, and antioxidant activities, indicating that these genotypes to be promising for further breeding program and commercial purposes.